38.8k views
1 vote
-6(y+15)=3y+6 What value of Y makes the expression true?

1 Answer

6 votes

Answer:


-(32)/(3) or -10.666666666666 or -10 2/3.

Explanation:

The question is asking what Y value makes them equal to each other. Thankfully you know that your primary (and only) goal is to isolate the y value and get it's numerical value.

First let's simplify the equation.

-6y-90=3y+6

Now lets do the PEMDAS operations to isolate Y and get it's numerical value.

-6y-90=3y+6

-6y-90-6=3y+6-6

-6y-96=3y

-96=9y


-(32)/(3) = y

User Rothloup
by
4.3k points